Facts about Protein - Nicole C. Argo; Wendy J. Dahl (EDIS)
There are many sources of dietary protein. This 3-page fact sheet covers protein basics, the role of proteins in the body, recommended intake, sources of protein, and how to make healthier choices. Written by Nicole C. Agro and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, January 2015.